Dyslexia [videorecording] symptoms & solutions - Barton, Susan M.; Barton, Susan M.; Bright Solutions for Dyslexia, LLC. (San Jose, Calif. Bright Solutions for Dyslexia, LLC., 2006)
"If you want to learn more about dyslexia and how it can be overcome, Susan Barton's dynamic, information-packed new DVD is for you. Filmed before a live audience, Susan's lively and captivating presentation provides insights, knowledge, techniques, and inspiration you just can't find anyplace else."--Container.
DVD 1. What is dyslexia ; Classic warning signs -- DVD 2. Reading mistakes ; Gifts & solutions.
Keywords: Dyslexia; Learning disabilities; Educational videos